Evaluating the results of multiprofessional health care on the glucemic control, lipid profile, and nutritional status of diabetic patients assisted at primary level - Rosado BATISTA, Maria da Conceição (2023)
ObjectiveThis work evaluates the multiprofessional intervention results on glucemic control, lipid profile, and nutritionalstatus of diabetic patients, who received primary level health care in Belo Horizonte, state of Minas Gerais,Brazil.MethodsAn examination was carried out, to evaluate the levels of glucemia, body mass index, and lipid profile of 190type-2 diabetic patients (31 to 83 years old), assisted during the period of 1993 to the year 2000. The datawere collected at the 1st. consultation on nutrition, and after three months, whereas some data were alsocollected at a 3rd. moment (6 months after the initial consultation).ResultsInitially, the registered data were the high average and medium values for body mass index, fasting glucemia,total cholesterol, LDL-c and triglycerides. Over the first three months after intervention, a significant reductionoccurred in the body mass index (from 28.3 to 27.8kg/m2), fasting glucemia levels (from 178.5 to 135.0mg/dL),total cholesterol (from 251.0 to 230.0mg/dL), LDL-c (from 185.5 to 159mg/dL) and triglycerides (from 243.0 to190.0mg/dL); however, no alteration occurred in the HDL-c levels. The patients with body mass index<30kg/m2, as well as those with a more recent history of diabetes obtained better outcomes.ConclusionThis study’s results allow us to conclude that multiprofessional health care is fundamental in controllingdiabetes, and such care should begin as soon as possible.